O uso de SIG na espacialização de dados oncológicos: o caso do Hospital de Clínicas de Uberlândia/UFU - Siqueira, Celso Antônio de (2004)
Information is a basic resource for all human activities and is equally vital for the management of health services, whose decisions go through the political fields as well. The epidemiologic data that exist in Brazil highlight cancer as a public health problem. Thus, the Geographic Information System (GIS) used for making maps and graphics from a database has shown to be an effective and appropriate instrument to assess the spatial distribution of Cancer in the area of influence of the Oncology Sector of the UFU (Federal University at Uberlandia) Clinic Hospital. Besides the data spatial location made, this work aims more objectively at the methodology, emphasizing the use of the GIS. This way, an eventual contribution to the popularization of such resource for Health affairs is also fulfilled. As a result of this study, some trends could be observed and confirmed: the admittance of the population of Uberlandia and vicinal cities prevail; and the attendance by the Oncology Sector/HCU/UFU is essential to those cities. Here, we can infer that the hospital covers highly over the 715,000 inhabitants of Uberlandia, number considered ideal to an adequate covering of cancer in Brazil. The characteristics that led GIS ArcView to be chosen were thoroughly confirmed as the application helped accomplishing the proposed objectives.